Poincare vector correlations to estimate polarization dynamics in the laser speckle - Chandra S.; Singh R.; Singh R.K. (My University, 2025)
We propose and experimentally demonstrate a new method to measure the spatial polarization dynamics of laser speckles. This is realized by using the concept of the Poincare vector correlations and experimentally measured Stokes parameters. Two-point correlations of the Stokes parameters offer a new and stable experimental technique to determine the Poincare vector correlations and characterize the polarization fluctuations of the laser speckle. The use of two-point Stokes correlations in the evaluation of spatial polarization dynamics offers a new method and the performance of this technique is tested by evaluating the spatial polarization dynamics of three different cases of the laser speckles. Experimental results are also tested and compared with the simulations results and good agreement between simulation and experimental results confirm the accuracy and usefulness of our technique in the characterization of the polarization dynamics. © 2023 IOP Publishing Ltd.